TREATMENT OF COMPLICATED CROWN ROOT FRACTURE WITH REATTACHMENT OF THE TOOTH FRAGMENT. A CASE REPORT - Georgieva-Dimitrova Milena (Romanian Society of Oral Rehabilitation, 2020)
Traumatic injuries take place in almost 25% of the children between age of 8 and 10. It is really important the medical intervention to be in time for better prognosis and clinical results. In the current clinical case of complicated crown-root fracture a decision of reattachment technique was taken for the restoration of the tooth, since the patient provided the fractured fragment. The choice of this clinical approach was provoked by patient's preference of fast and esthetic result. The best way to achieve this was to reattach the fragment supported by fiber post build-up which provided good outcomes in short term and relatively high retention of the restoration. The tooth was endodontically treated in advance.